The right of persons with sensory disabilities to educational inclusion in the Supreme Federal Court (Research, Society and Development, 2020)
This research aims to systematize cases related to the educational inclusion of people with sensory disabilities, judged by the Supreme Federal Court (STF), identifying empirical matter involved in the realization of the right securitized to this historically excluded minority. The research used the deductive approach method, and it has a descriptive nature, and used technical, bibliographic and documentary procedures. The right to education is defined as a fundamental human right, highlighting its genesis in the context of the recognition of positive freedoms, the human, political and economic dimensions, and also its progressive universalization given through the process of public policy that combines state efforts, economic initiatives and third sector activities. It also describes the effects of long years of exclusion of people with disabilities in the educational context, which overcoming has been constituted as a political-legal imperative in the interpretation and application of the law by the Brazilian Supreme Court. The systematization demonstrates that the achievement of the right of people with sensory disabilities to education involves: accessible educational environment; specialized and school support professionals; assistive technology; specialized educational services in inclusive or special institutions; and broad non-discriminatory access to private educational institutions. Finally, it concludes by highlighting the contribution of jurisprudence in the multidimensional process of educational inclusion.